The Influence of Work Environment and Work Discipline on Employee Performance at Simokerto District Office Through Work Motivation as a Mediating Variable - Sawitri, Elly; sutarso, Yudi (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the effect of work environment and work discipline on employee performance at Simokerto District Office with work motivation as a mediating variable. Using a quantitative approach with SEM-PLS on 113 respondents, results reveal that work environment and discipline significantly influence motivation and performance. Motivation also significantly mediates these effects. The study highlights the need for improving workplace conditions and discipline to enhance performance. Implications suggest local government should prioritize creating a supportive environment and enforcing clear discipline policies to strengthen employee motivation, thereby ensuring better service delivery and organizational effectiveness.